Pengaruh Pemasaran Digital terhadap Pertumbuhan Volume Penjualan Cabai Rawit di Kolaka Timur Indonesia - Rika Sulastri; Hartati Hartati; Syamsinar Syamsinar (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
This research investigates how the use of digital marketing contributes to the growth of bird’s eye chili sales in East Kolaka Regency. The research was conducted in 2024 with 30 chili farmers selected through purposive sampling. The variables studied included digital marketing practices (X) and the resulting sales volume (Y). A quantitative approach was applied, utilizing linear regression to assess the influence of the independent variable on the dependent variable. Data were obtained using structured questionnaire instruments. The study’s results demonstrate that digital marketing has a significant, positive impact on the sales volume of bird’s eye chili. These outcomes underscore the growing relevance of digital marketing in the agricultural sector and highlight the need to improve farmers’ digital skills and access to online platforms.